Digital Twin for Designing and Reconfiguring Human–Robot Collaborative Assembly Lines - Niki Kousi; Christos Gkournelos; Sotiris Aivaliotis; Konstantinos Lotsaris; Angelos Christos Bavelos; Panagiotis Baris; George Michalos; Sotiris Makris (Applied Sciences, 2021)
This paper discusses a digital twin-based approach for designing and redesigning flexible assembly systems. The digital twin allows modeling the parameters of the production system at different levels including assembly process, production station, and line level. The approach allows dynamically updating the digital twin in runtime, synthesizing data from multiple 2D–3D sensors in order to have up-to-date information about the actual production process. The model integrates both geometrical information and semantics. The model is used in combination with an artificial intelligence logic in order to derive alternative configurations of the production system. The overall approach is discussed with the help of a case study coming from the automotive industry. The case study introduces a production system integrating humans and autonomous mobile dual arm workers.